Pengaruh Motivasi Belajar Terhadap Hasil Belajar Matematika Peserta Didik - Chatarina Novianti; Berty Sadipun; John M Balan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine (1) learning motivation towards mathematics learning outcomes for Ende 11 students in Ende Regency. (2) learning outcomes of students of SDI Ende 11, Ende Regency. (3) to prove whether there is an influence of learning motivation on mathematics learning outcomes of SDI Ende 11 students. The sampling technique was done purposively on a questionnaire that was made in order to obtain actual data. The instrument of this study was the questionnaire and documentation of students' mathematics learning outcomes in SDI Ende 11. Data analysis techniques used product moment analysis analysis. The results of the study showed that the hypothesis testing obtained Fcount = 14.598 and Ftable = 4.20, meaning that there was a significant influence between learning motivation towards mathematics learning outcomes of classes III, IV and V SDI Ende 11. So the regression equation can be used to predict or predict the magnitude of the criterion variable (Y) based on the predictor variable (X). The results of these analysts prove that the constant coefficient on the linear model is 0.001 significantly smaller than 0.05, meaning that the regression coefficient of mathematics learning outcomes is significant. Conclusion, the effect value is R Square = 0.343, this value implies that the influence of learning motivation on mathematics learning outcomes is 34.3% and 65.7% is determined by variables or other factors. Keywords: Learning Motivation, Mathematics Learning Outcomes